Organization and phylogenetic relationships of the mitochondrial genomes of Speiredonia retorta and other lepidopteran insects - Yu Sun (Nature Portfolio, 2021)
Abstract In this study, we analyzed the complete mitochondrial genome (mitogenome) of Speiredonia retorta, which is a pest and a member of the Lepidoptera order. In total, the S. retorta mitogenome was found to contain 15,652 base pairs encoding 13 protein-coding genes (PCGs), 22 tRNAs, 2 rRNAs, as well as an adenine (A) + thymine (T)-rich region. These findings were consistent with the mitogenome composition of other lepidopterans, as we identified all 13 PCGs beginning at ATN codons. We also found that 11 PCGs terminated with canonical stop codons, whereas cox2 and nad4 exhibited incomplete termination codons. By analyzing the mitogenome of S. retorta using Bayesian inference (BI) and maximum likelihood (ML) models, we were able to further confirm that this species is a member of the Erebidae family.